2012
DOI: 10.1089/jwh.2011.3220
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Association of Age with Carotid Artery Distensibility: Multi-Ethnic Study of Atherosclerosis

Abstract: Background: Older women have a higher prevalence of systolic hypertension than do men; however, whether or not this relates to arterial properties, such as distensibility coefficient (DC), is not known. We examined whether the association of carotid artery DC with age differed by sex in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: B-mode ultrasound-measured carotid diameters and brachial pressures were obtained from 6359 participants (53% female, 38% white, 12% Chinese, 27% black, 22% Hispanic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…7 Sex-related differences in the effects of antihypertensive therapy on distensibility progression may reflect lower control rates in older hypertensive women than men despite greater awareness and higher treatment rates among women. 18,19 Though some studies reported non-significant differences in control rates by sex, 20 our data shows that among treated hypertensives at baseline, men had better hypertension control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Sex-related differences in the effects of antihypertensive therapy on distensibility progression may reflect lower control rates in older hypertensive women than men despite greater awareness and higher treatment rates among women. 18,19 Though some studies reported non-significant differences in control rates by sex, 20 our data shows that among treated hypertensives at baseline, men had better hypertension control.…”
Section: Discussionmentioning
confidence: 99%
“…2 Pathophysiological changes induced by hypertension include increased total peripheral resistance and decreased arterial compliance, ultimately limiting arterial distensibility. 2 An analysis from the Multi-Ethnic Study of Atherosclerosis (MESA) showed significant cross-sectional differences between the sexes in carotid distensibility; 7 however, longitudinal sex-related differences in age-related arterial stiffening and its predictors have not been described previously.…”
Section: Introductionmentioning
confidence: 99%
“…13 The slope Δ(logA)/ΔP was calculated directly within regression models adjusting for the confounders of both A and P in a single step. 14 The excursions from the mean of the systolic and diastolic pressures, together constituting pulse pressure as separate observations for each individual were added to the mixed regression model, while the mean of systolic and diastolic pressures was added as a covariate. Individual-level pulse-cycle mean log(area), as well as the individual level slope of log(area) vs. pressure between systole and diastole were estimated as random effects, and group-level differences in diameter and slopes are estimated as fixed effects.…”
Section: Methodsmentioning
confidence: 99%
“…Larger carotid artery diameter has also been shown to be associated with aging and cardiovascular risk factors. [23] Other studies that have shown that BAD is associated with carotid artery diameter and left ventricular mass[24] as well as right ventricular mass. [25]…”
Section: Discussionmentioning
confidence: 99%